Parents Social Economic, Physical Activity, and Formula Milk Consumption with Obesity for Toddlers In The Working Area of Puskesmas Sidayu, Gresik District. - Durrotun Nasihah (Universitas Muhammadiyah Gresik, 2021)
The incidence of obesity in Indonesia is increasing every year. In 2017, according to survey data on Nutrition Status Monitoring (PSG, 2015) stated that the prevalence of obese children under five in Indonesia according to body weight was 5,63%. Obese toddlers tend to have a poor quality of life. The purpose of this study was to see the social economic of parents, physical activity, and consumption of formula milk with obesity for toddlers. This research are a descriptive analytic study with a cross sectional approach. This research was conducted from August 2020. The sample in this study were children aged 1-5 years who were obese, totaling 43 respondents. Data collection used a parent socioeconomic questionnaire, EY-PAQ (Early Year-Physical Activity Questionnaire) questionnaire, and instans formula milk consumption questionnaire. Based on the results of data analysis using the chi square test, it showed that parents' social economic, physical activity and consumption of formula milk with obeseity in toddlers group have no significant relationship as evidenced by a p value> 0.05. From this study it can be concluded that there is no relationship between the social economic of parents, physical activity, and consumption of formula milk with obesity for toddlers.